Mortality from fall: A descriptive analysis of a multicenter Indian trauma registry. Issue 12 (December 2022) - Basak, Debojit; Anthony, Aroke Anna; Banerjee, Niladri; Rath, Santosh; Chatterjee, Shamita; Soni, Kapil Dev; Sharma, Naveen; Ogawa, Takahisa; O'Reilly, Gerard; Attergrim, Jonatan; Wärnberg, Martin Gerdin; Roy, Nobhojit
Highlights: Fall is the second leading cause of unintentional injury mortalities worldwide. Isolated TBI and TBI associated with other injuries are the major contributors of mortality in injuries associated with fall. Mortality is directly proportional to age and ISS in patients with history of fall. Abstract: Introduction: Fall is the second most common mechanism of trauma worldwide after road traffic injuries. Data on fall predominantly comes from the high-income countries (HICs) and mostly includes injuries in children and elderly. There are very few studies from low- and middle-income countries(LMICs) that describe fall related injuries other than fragility fractures in elderly. This study describes the profile of poly-trauma patients admitted with a history of 'fall' and assesses the variables associated with mortality. Method: We analyzed data from the 'Towards Improved Trauma Care Outcome' (TITCO) database which prospectively collected data of poly-trauma patients admitted to four major tertiary care hospitals of India between 2013 to 2015. Patients across all age groups admitted to hospital with the history of 'fall'; were included in our study. Single bone fractures were excluded.  The Kaplan Meier survival analysis was used to estimate the survival probability in different age groups. Results: A total of 3686 patients were included in our study. The median age of the patients was 28 years (IQR: 9, 47) with the majority being males (73.6%). Almost one-third of the patients were within the age group of 0-14 (30.4%). Most of the patients (79.9%) had a diagnosis of traumatic brain injury (TBI). The overall in-hospital mortality was 18% (664), but higher at 39.0% among patients over 65 years of age. Probability of survival decreased with increase of age. Conclusion: Falling from height is a common injury mechanism in India, occurring more in young males and usually associated with TBI. Isolated TBI and TBI associated with other injuries are the main contributors of mortality in fall injuries. Mortality from these injuries increased with age and ISS.